Prospective and Randomized Evaluation of ChronOS and Bio-Oss in Human Maxillary Sinuses: Histomorphometric and Immunohistochemical Assignment for Runx2, Vascular Endothelial Growth Factor, and Osteocalcin - Bonardi, Joao Paulo [UNESP]; Pereira, Rodrigo dos Santos [UNESP]; Jorge Boos Lima, Fernanda Brasil Daura; Faverani, Leonardo Perez [UNESP]; Griza, Geraldo Luiz [UNESP]; Okamoto, Roberta [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Elsevier B.V., 2018)
Purpose: The aim of this study was to compare ChronOS (beta-tricalcium phosphate), Bio-Oss, and their addition to an autogenous bone graft in a 1: 1 ratio in human maxillary sinus bone augmentation. Materials and Methods: Thirty maxillary sinuses were divided in 5 groups: group 1 included 6 maxillary sinuses grafted with autogenous bone graft alone; group 2 included 6 maxillary sinuses grafted with ChronOS; group 3 included 6 maxillary sinuses grafted with ChronOS and autogenous bone graft in a 1: 1 ratio; group 4 included 6 maxillary sinuses grafted with Bio-Oss; and group 5 included 6 maxillary sinuses grafted with Bio-Oss and autogenous bone graft in a 1: 1 ratio. The number of samples for each group was determined by the statistical power test. Results: The median areas of new bone formation in groups 1, 2, 3, 4, and 5 were 121,917.0, 83,787.0, 99,295.0, 65,717.0, and 56,230.0 mu m(2), respectively. Statistically significant differences were found between groups 3 and 5, groups 1 and 4, and groups 1 and 5 (P <.05). The median areas of remaining biomaterial were 2,900.5, 5,291.0, 2,662.0, 56,258.5, and 64,753.5 mu m(2) in groups 1, 2, 3, 4 and 5, respectively. Statistically significant differences occurred between groups 1 and 5, groups 3 and 5, and groups 2 and 5 (P <.05). Areas of connective tissue were 67,829.0 +/- 22,984.6 mu m(2) in group 1, 97,445.9 +/- 18,983.3 mu m(2) in group 2, 88,256.0 +/- 21,820.5 mu m(2) in group 3, 65,501.8 +/- 6,297.6 in group 4, and 70,203.2 +/- 13,421.3 mu m(2) in group 5. Conclusions: ChronOS combined with autogenous bone graft presented a behavior similar to that of autogenous bone graft alone. However, the groups treated with Bio-Oss showed immuno-labeling results indicating maturation of grafted bone. (C) 2017 American Association of Oral and Maxillofacial Surgeons